2014
DOI: 10.1186/s12933-014-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pitavastatin versus atorvastatin on the peripheral endothelial progenitor cells and vascular endothelial growth factor in high-risk patients: a pilot prospective, double-blind, randomized study

Abstract: BackgroundCirculating endothelial progenitor cells (EPCs) reflect endothelial repair capacity and may be a significant marker for the clinical outcomes of cardiovascular disease. While some high-dose statin treatments may improve endothelial function, it is not known whether different statins may have similar effects on EPCs.This study aimed to investigate the potential class effects of different statin treatment including pitavastatin and atorvastatin on circulating EPCs in clinical setting.MethodsA pilot pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In patients who were prescribed statins, discontinuation and poor adherence were common in clinical practice, which limits assessing the diabetogenic effect of statins [ 72 ]. The effect of statins on glucose metabolism are complex and interconnected by multiple pathways; individual statins may have a heterogenous impact on the multiple processes [ 11 ]. To obtain further knowledge of individual statins on glucose metabolism, there is need for further extensive studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients who were prescribed statins, discontinuation and poor adherence were common in clinical practice, which limits assessing the diabetogenic effect of statins [ 72 ]. The effect of statins on glucose metabolism are complex and interconnected by multiple pathways; individual statins may have a heterogenous impact on the multiple processes [ 11 ]. To obtain further knowledge of individual statins on glucose metabolism, there is need for further extensive studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still insufficient data for the longitudinal changes in fasting glucose with the use of statins. In addition, there are multiple types of statin, each with a different chemical structure and pharmacokinetic profile [ 11 , 12 ]. The individual statin types may have different effects on glucose metabolism [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous considerations, anti-diabetic drugs effective in enhancing EPC number may convey an added value, beyond glucose control, to reduce CV risk and to prevent CV disease in patients with type 2 diabetes. A number of anti-diabetic drugs, namely pioglitazone [ 6 ] and insulin [ 7 ], and statins [ 8 ] have been shown to improve EPC biology in ex vivo studies. Recent evidence points to a potential role of dipeptidyl peptidase-4 inhibitors (DPP-4i) in increasing circulating EPC number.…”
Section: Introductionmentioning
confidence: 99%
“…A double blinded randomised pilot study found greater number of circulating CD34 + VEGFR-2 + EPCs after 12 wk of therapy with pravastatin 20 mg when compared to atorvastatin 10 mg[97]. Similarly, in ACS patients’ intensive statin therapy with atorvastatin 80 mg after primary or rescue PCI was associated with greater EPC count at 4-mo follow up as compared to 20 mg atorvastatin.…”
Section: The Effect Of Statin Therapy On Epcsmentioning
confidence: 99%